Origin of overpressure in a field in the southwestern Malay basin - Satti, I.A. (Society of Petroleum Engineers, 2015)
This study demonstrates the use of wireline logs for the overpressure-mechanisms analysis in a field in the southwestern Malay basin. The development of overpressure means that the fluid movement in the pores is retarded, both vertically and laterally. In many Tertiary basins, overpressure is mainly generated by compaction disequilibrium caused by a high deposition rate and low permeability in shales. In the Malay basin, temperature and high-heat flow also play an important role in generating overpressure at a shallow depth, because the geothermal gradient is very high (40-60Â°C/km). Pore-pressure profiles and crossplots of sonic velocity/vertical effective stress and of velocity/density are used to derive the overpressure-generating mechanisms. The results obtained from the crossplots of 10 wells reveal that in the study area, overpressure is generated by both primary (compaction-disequilibrium) and secondary (fluid-expansion) mechanisms. The overpressure-magnitude analysis suggests that the overpressure generated by the secondary mechanism is very high compared with the primary mechanism. In all the wells, the Eaton (1972) method with an exponent of 3 gives good prediction when overpressure is the result of the compaction-disequilibrium mechanism, but it underpredicted the high pore pressure where the fluid-expansion mechanism is also present. However, by use of a higher Eaton exponent of 5 for the fluid-expansion mechanism, the overpressures are predicted quite well. The Bowers (1995) method, by use of the unloading parameter (U) of 6, is also used for pressure prediction and it gives a reasonably good prediction in the high-overpressure zone of all the wells. Copyright Â© 2015 Society of Petroleum Engineers.